Answer:
p=37
Step-by-step explanation:
to get p by its self, you would do:
p+36=73
-36=-36
p=37
Answer:
A.
Step-by-step explanation:
y = mx + c
m = y - y¹ / x - x¹
= 4-3 / 4-2
= 1/2
using (4,4)
4 = 1/2 × 4 + c
4 = 2 + c
c = 2
equ..=
y = 1/2x + c
The equation that passes through these points is x = 4
Find the area of one side, which is length x width:
2/3 x 2/3 = 4/9 square ft.
There are 6 sides to the prism, so multiply the area of one side by 6:
4/9 x 6 = 24/9 = 2 6/9 = 2 2/3 square ft.
work shown above! basically each coordinate is opposite so the new coordinates would be A(0,-3) B(-2,4) C(4,6)